Social responsibility program: FPHP UiTM Cawangan Pulau Pinang and Garden Village Design Sdn. Bhd. / Khairul Hidayat Rezo ... [et al.] - Rezo, Khairul Hidayat; Micheal, Sperico; Razali, Mohd Azli; Mohamad Saber, Joesri (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2023)
Community service is an activity of paramount importance in fostering a sense of unity among the community and the UiTM Cawangan Pulau Pinang residents. It nurtures a spirit of mutual respect and concern for the local community. Through community service, individuals apply their knowledge, skills, and civic values in a meaningful way. On February 10, 2023, the Community Service and Knowledge Transfer Program (KTP) took place at the Laman Damain in Taman Pauh, Permatang Pauh. The event was organized by Garden Village Design Sdn. Bhd. (GVDSB) in collaboration with the Faculty of Hotel and Tourism Management, UiTM Cawangan Pulau Pinang where it was a resounding success. The "Social Responsibility" program was inaugurated by YBhg. Dato’ Azman Ibrahim, the Director of State Development (ICU) for Penang. This social responsibility program was divided into four sessions: a Cooking Demonstration by Chef Mohamad Azli Razali, a Barista Demonstration by Mr. Mohd Zool fadli Ibrahim, an explanation of the solar system for industry players by Associate Professor Ir. Dr. Nor Azlan Othman, and a session for distributing aid to deserving beneficiaries. A total of 10 beneficiaries, who were the cleaning and maintenance staff at UiTM, received assistance in the form of hampers and daily necessities.